The Work of the International Law Commission: Ninth Edition - United Nations Office of Legal Affairs (United Nations, 2017)
The present publication is intended to provide a general introduction to the work of the International Law Commission. Volume I contains a discussion of the nature and role of the Commission, as well as of its programme of work, working methods and relationship with Governments and other legal bodies. It also includes a brief summary of the work undertaken on each topic considered since 1949, as well as several annexes, containing its Statute and relevant historical information about the Commission. A selected bibliography of materials related to the work of the Commission is appended. The present edition reflects the latest developments in the work of the Commission as of 31 December 2016. (Two-Volume Set)